The place of pharmacy ethics during pharmacy education and training targets - Özcömert, Gülsüm Hale; Görkey, Şefik (Marmara Üniversitesi Sağlık Bilimleri Enstitüsü Dergisi, 2012)
Education is equipping persons with knowledge and skills. The most important issue at this point is to inform the students about the futureof this profession. Necessary importance is not given to ethics during pharmacy education. Graduated pharmacists, graduate their schools without having enough sensitivity on this subject. As a result, during the pharmaceutical practices in the field more ethical problems are faced. Ethics education to be given in prevocational training and vocational retraining with more detailed and more rational teaching methods is a fact. In this study, the level of teaching of ethics in world and in Turkey faculty of pharmacy is searched, the world and Turkey’s faculty of pharmacy of the web sites & programs have been reached, the department of the respective faculty members were interviewed. To provide better ethics education more efficient, a program with suitable educational targets for our country was proposed.
Keywords: Ethics, pharmacy ethics, ethics education, pharmacy ethics education, pharmaceutical deontology